Great Theorists of Central European Integration in Ukraine - Fedinec, Csilla (Great Theorists of Central European Integration, 2023)
‘Central Europe’ is a concept that varies in time and space. Ukraine is the second-largest country on the European continent, and is geographically located south-west of the Eastern European plain. The peculiarity of historical development and geographical location leads to the portrayal of Ukraine as a civilizational frontier area between the countries of the West and East. The nineteenth century was the period of birth of national histories, equally among non-historical (stateless) and historical (state) nations, while at the same time, at any historical moment, one can find the predecessor of the modern nation. The coherence of the Ukrainian narrative is ensured by proto-state and state forms: Kyivan Rus, the Principality of Galicia-Volhynia, Polish-Lithuanian Commonwealth, Cossack era, Ukrainian statehood in 1917–1921, Soviet era, Carpatho-Ukraine’s autonomous existence in 1938–1939, and independent Ukraine since 1991. The Kyivan Rus was oriented towards Byzantium, and the Principality towards Western Europe. The Hetmanate’s political structure recognised as a historical Cossack statehood. In the mid-17th century, the Cossack uprising led by Bohdan Khmelnytsky brought to the fore the dilemma of pro Moscow or pro-Polish (in fact, pro-European) orientation. Since the late 18th century, Ukrainian territories have become the periphery of the empires, and ties with Europe have weakened. Europe almost forgot about Ukraine’s existence. The central powers of the First World War attempted to tear Ukraine away from Russia and push it politically and civilizationally towards the West, albeit without any international interest in the question of Ukrainian statehood aspirations. Later, the Soviet Union created Ukrainian borders, but deprived the Ukrainians of any political activity. Pro-European Union tendencies were always present in independent Ukraine, but only took definite shape following the Revolution of Dignity in 2014. In 2014 Ukraine and the European Union signed the Association Agreement, came into effect in 2017. Russia’s disastrous full-scale invasion against Ukraine accelerated Ukraine–EU rapprochement, and as a result Ukraine was granted EU candidate status in 2022. Europeanisation is not only a process of identity construction, but also a value-based supranational ‘ways of doing things’. In this context, Ukraine’s place in the buffer zone between Eastern and Western Europe has changed over the centuries. The study analyses the development of opinions on this topic, based on the works of some selected Ukrainian and Ukrainian-descent thinkers from the 19th century to the present day. KEYWORDS: Ukraine, Central Europe, East and West dichotomy, nation, nationalism, historical development